Autoimmune polyglandular syndrome among Chinese celiac disease patients: a survey of 243 individuals in China - Xue, Shenglong; Feng, Yan; Shi, Tian; Halike, Halina; Maimaitireyimu, Ayinuer; Abudurexiti, Adilai; Xie, Jinjin; Yao, Shanxia; Gao, Feng (Frontiers in Immunology, 2025)
BackgroundCeliac disease (CeD), an autoimmune enteropathy, is often associated with multiple glandular autoimmune diseases. However, the prevalence and staging characteristics of autoimmune polyglandular syndrome (APS) among CeD patients remain unclear. The aim of this study was to assess the prevalence and clinical features of APS among Chinese CeD patients.MethodsClinical data and medical records of 243 CeD patients diagnosed in northwest China were retrospectively analyzed to identify comorbid autoimmune diseases among CeD patients. Serum interferon-ω1, interferon-α, and thyroid autoantibodies (TPOAb and TgAb) were measured, and AIRE mutations were detected. APS typing was conducted based on serum antibodies, gene sequencing (AIRE mutation analysis), and comorbidity analysis.ResultsThe overall prevalence of APS in CeD patients was 10.3% (25/243), and the prevalence of different types of APS varied as follows: APS-1: 0.4%, APS-2: 0.4%, APS-3: 8.2%, and APS-4: 1.2%. The prevalence of APS in CeD patients was significantly higher than that in the general population, especially the prevalence of APS-3. Patients with CeD combined with APS had a higher prevalence of vitamin D deficiency (13 of 25 patients, 52%) and H. pylori infection (8 of 25 patients, 32%). In addition, CeD patients with combined APS were more likely to have anxiety and depressive symptoms (P < 0.05), but there were no significants differences in gender, ethnicity, or body mass index.ConclusionThis study is the first to systematically evaluate the prevalence and staging characteristics of APS among CeD patients, thereby filling the epidemiological data gap in this area. We emphasize the significance of screening for APS among CeD patients to enable early detection and treatment of associated autoimmune diseases and enhance patients’ quality of life.